Penghijauan Kawasan Geosite Banyu Wedang dan Aksi Kerja Bakti di Area Selo Gajah: Upaya Konservasi dan Pemberdayaan Komunitas Berbasis Geowisata di Desa Jari - Indriani, Yulia; Pratama, Irfan Adi; Putri, Kharisma Eka; Aji Prayogo, Dimas Priyo; Ariyono, Edo Prasetyo (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Geotourism-based environmental conservation activities are a strategic effort to preserve geosites and raise public awareness of the importance of earth's heritage. Jari Village, Gondang District, Bojonegoro Regency, has the potential for geotourism in Banyu Wedang and Selo Gajah. This area is relatively arid and has minimal vegetation, necessitating geotourism-based conservation efforts involving the surrounding community. These activities aim to increase the local community's sense of ownership of the geosite, improve the ecology of the geosite, and enhance the area's aesthetic value to support geotourism development. The implementation method includes area surveys, planning and coordination, environmental education, and implementation. The 15 trees planted in Banyu Wedang are primarily food crops, consisting of 10 mango trees and 5 guava trees, as well as land clearing around Selo Gajah. The results of these activities demonstrate active community participation in tree planting in Banyu Wedang and community service at Selo Gajah. These activities are expected to enhance the area's aesthetics, prevent erosion, and raise awareness of geosite-based conservation.